Cockroach allergen serine proteinases: Isolation, sequencing and signalling via proteinase-activated receptor-2 (PAR2) - Polley, Danny J. (Clin Exp Allergy, 2017)
BACKGROUND: Allergy to the German cockroach (Blattella germanica) is a significant asthma risk factor for inner-city communities. Cockroach, like other allergens, contains trypsin-like enzyme activity that contributes to allergenicity and airway inflammation by activating proteinase-activated receptors (PARs). To date, the enzymes responsible for the proteolytic activity of German cockroach allergen have not been characterized. OBJECTIVES: We aimed to identify, isolate and characterize the trypsin-like proteinases in German cockroach allergen extracts used for clinical skin tests. For each enzyme, we sought to determine (1) its substrate and inhibitor enzyme kinetics (Km and IC50); (2) its amino acid sequence and (3) its ability to activate calcium signaling and/or ERK1/2 phosphorylation via PAR2. METHODS: Using a trypsin-specific activity-based probe, we detected three distinct enzymes that were isolated using ion-exchange chromatography. Each enzyme was sequenced by mass spectometery (deconvoluted with an expressed sequence tag library), evaluated kinetically for its substrate/inhibitor profile and assessed for its ability to activate PAR2 signaling. FINDINGS: Each of the three serine proteinase-activity-based probe-labelled enzymes isolated were biochemically distinct, with different enzyme kinetic profiles and primary amino acid sequences. The three enzymes showed a 57 to 71% sequence identity with a proteinase previously cloned from the American cockroach (Per a 10). Each enzyme was found to activate both Ca(++) and MAPK signaling via PAR2. CONCLUSIONS AND RELEVANCE: We have identified three different serine proteinases from the German cockroach that may, via PAR2 activation, play different roles for allergen-sensitization in vivo and may represent attractive therapeutic targets for asthma.